Comparison of Standardized Cytomegalovirus (CMV) Viral Load Thresholds in Whole Blood and Plasma of Solid Organ and Hematopoietic Stem Cell Transplant Recipients with CMV Infection and Disease. (8th July 2017) - Dioverti, M Veronica; Lahr, Brian D; Germer, Jeffrey J; Yao, Joseph D; Gartner, Michelle L; Razonable, Raymund R
Abstract: Background: Quantification of cytomegalovirus (CMV) deoxyribonucleic acid (DNA) has important diagnostic, prognostic, and therapeutic implications in the management of transplant recipients. We aimed to assess a viral load in plasma and whole blood that distinguishes CMV disease from asymptomatic infection in a cohort of solid organ and hematopoietic stem cell transplantation. Methods: We prospectively measured and compared CMV viral load in paired plasma and whole blood samples collected from transplant recipients with CMV infection and disease. Cytomegalovirus viral loads were determined by a commercially available US Food and Drug Administration-approved quantitative assay (COBAS AmpliPrep/COBAS TaqMan CMV Test [CAP/CTM CMV]) calibrated to the first World Health Organization International Standard for CMV DNA quantification. Results: Moderate agreement of CMV viral load was observed between plasma and whole blood, with 31% of samples having discordant findings, particularly among samples with low DNA levels. Among the subset of samples where both paired samples had quantifiable levels, we observed a systematic bias that reflected higher viral load in whole blood compared with plasma. Based on receiver operating curve analysis, an initial plasma CMV viral load threshold of 1700 IU/mL in solid organ transplant recipients (sensitivity 80%, specificity 74%) and 1350 IU/mL in allogeneic hematopoietic stem cell transplant recipients (sensitivity 87%, specificity 87%) distinguished CMV disease and asymptomatic infection. Conclusions: This study identifies standardized viral load thresholds that distinguish CMV disease from asymptomatic infection using CAP/CTM CMV assay. We propose these thresholds as potential triggers to be evaluated in prospective studies of preemptive therapy. Plasma was better than whole blood for measuring viral load using the CAP/CTM CMV assay.